#TITLE_ALTERNATIVE# - HERNAWAN (NIM 12206006); Pembimbing: Ir. Tutuka Ariadji, M.Sc., Ph.D., ARISTYA
Sensitivity analysis show that increasing the value of storativity ratio will increase the oil flow rate by 0.5% to 1.8% and increasing the value of interporosity flow coefficient will decrease the oil flow rate by 0.05% to 0.9%. Sensitivity was also conducted on the horizontal well length that gives the result that increasing the length of the horizontal well will increase the oil flow rate by 10.3% to 18.9%. The combined analysis of these three parameters will form the equation of oil flow rate with high accuracy for the cases studied. The productivity index of homogeneous reservoir which is obtained from the Joshi's equation require a correction before being used in the proposed equation.